Outcomes of Hodgkin variant Richter transformation in chronic lymphocytic leukaemia and small lymphocytic lymphoma in British Columbia. (14th May 2022) - Zhu, Kai; Jamroz, Andrew; Huang, Steven; Villa, Diego; Freeman, Ciara L.; Scott, David W.; Slack, Graham; Sehn, Laurie H.; Connors, Joseph M.; Toze, Cynthia L.; Savage, Kerry J.; Gerrie, Alina S.
Summary: Hodgkin variant Richter transformation (HvRT) is a rare and challenging complication of chronic lymphocytic leukaemia (CLL) for which information on prognostic factors and treatment approaches remain limited. We analysed characteristics and survival outcomes of a population‐based cohort of 32 patients with HvRT identified in British Columbia over a 40‐year period. Median interval from CLL diagnosis to HvRT was 5.6 years (range, 0–33.6), with five cases diagnosed concurrently. Most patients (80%) had treatment for CLL prior to HvRT. Median age at HvRT was 71 years (range, 51–86) and the majority of patients had high‐risk disease, including stage 3–4 in 87% and International Prognostic Score (IPS) ≥ 4 in 65%. Two‐year progression‐free (PFS) and overall survival (OS) from HvRT were 47% (95% CI: 29%–64%) and 57% (95% CI: 38%–72%), respectively. OS from HvRT was significantly worse in those with anaemia ( p  = 0.02), elevated lactate dehydrogenase ( p  = 0.04), high IPS ( p  = 0.04), and worse performance status ( p  = 0.001). For those treated with curative‐intent ABVD/ABVD‐like therapy, 2‐year PFS and OS were 70% (95% CI: 45%–85%) and 74% (95% CI: 49%–89%), respectively. In this real‐world population‐based cohort, HvRT was associated with poor clinical outcomes overall; however, those able to tolerate curative‐intent therapy had similar survival to older patients with de novo HL.